Role Play Negosiasi Sebagai Bahan Ajar Digital Teks Negosiasi - Setiartin R, Titin; Alia, Fany Haifa; Nurhayati, Nita; Pitrianti, Siti; Annisa, Amelia Nurfitri (Universitas Negeri Padang, 2024)
Indonesian language learning in secondary schools directs students to be skilled in communicating according to Learning Objectives. Negotiation is one of the communication skills learned by students at the secondary school level. In the Independent Curriculum, Negotiation is a Learning Outcome that must be achieved by students. Negotiation role play in Indonesian language learning in secondary schools aims to explore various aspects of the Indonesian language, such as vocabulary, grammar, and communication skills, through negotiation simulations in real-life contexts. The creation of negotiation role play products uploaded by secondary school students must meet the criteria for structure, language rules, and communicative politeness patterns. This study aims to: 1) Describe the structure, language, and politeness patterns of negotiation role play uploaded on YouTube. 2) Describe the suitability of negotiation role play with negotiation text. 3) Describe the suitability of negotiation role play as digital teaching material. The research is included in descriptive analytical research with a structural approach and a pragmatic approach. The subject of the research is the negotiation text role play uploaded on the digital media YouTube. The research data was processed using qualitative descriptive analytical techniques. The results of the study conducted by calculating the percentage that the negotiation role play in learning Indonesian in the structure section has a conformity with a percentage of 100%, linguistic conformity of 77.7%, and conformity of politeness patterns has a percentage of 75%, the percentage is calculated by dividing the score obtained by the maximum score, then multiplied by 100%. This proves that the multiliteracy of negotiation role play on YouTube as Indonesian language teaching materials in high schools is in accordance with the criteria of negotiation texts as teaching materials.